2019
DOI: 10.3390/ma12182967
|View full text |Cite
|
Sign up to set email alerts
|

Laser Welding of SLM-Manufactured Tubes Made of IN625 and IN718

Abstract: The advantage of selective laser melting (SLM) is its high accuracy and geometrical flexibility. Because the maximum size of the components is limited by the process chamber, possibilities must be found to combine several parts manufactured by SLM. An application where this is necessary, is, for example, the components of gas turbines, such as burners or oil return pipes, and inserts, which can be joined by circumferential welds. However, only a few investigations to date have been carried out for the welding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…To obtain larger parts, one solution is to weld small parts. Laser welding enables a high-power density for a low-heat-energy input and high cooling rates [12,13]. These welding characteristics make it possible to weld thin parts, such as those obtained by SLM.…”
Section: Aisi 316l (316lmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain larger parts, one solution is to weld small parts. Laser welding enables a high-power density for a low-heat-energy input and high cooling rates [12,13]. These welding characteristics make it possible to weld thin parts, such as those obtained by SLM.…”
Section: Aisi 316l (316lmentioning
confidence: 99%
“…Moreover, the SLM and new welding lasers exploit the same technique (Yb: YAG); therefore, the same laser-matter interaction is expected. These similarities may minimize microstructure changes in samples produced by SLM [12]. Therefore, laser welding is a promising technique by which to join small additive manufactured parts.…”
Section: Aisi 316l (316lmentioning
confidence: 99%
“…The adaptation of the welding technology of the longitudinal weld to the circumferential weld required correction at the end of the weld. For this purpose, the known approach of reducing the power was used, described, e.g., by Jokisch et al [47]. A circular, symmetrical weld without undercuts, pores, and cracks is visible.…”
Section: Examination a Container Prototypementioning
confidence: 99%
“…Moreover, high heat inputs led to low weld quality, whereas slower welding speeds resulted in welds with higher quality. Jokish et al 11 demonstrated the general applicability of laser beam welding for joining SLM tube connections made of nickelbased alloys. However, numerous weld defects were observed, e.g.…”
Section: Introductionmentioning
confidence: 99%